Factors that Influence MSMEs Using Digital Payments - Faizah, Iva; Siregar, Susi Enggana (Journal of Islamic Financial Technology, 2023)
study This aim for know factors that influence MSMEs use digital payments ie covers factor barriers and factors supporting Micro, Small and Medium Enterprises in use digital payments. Study This is study qualitative. Data sources used in study This is using primary data and secondary data. Data collection techniques used in study This that is observation, interviews and documentation. Analysis of the data used in study This that is data reduction, data presentation and withdrawal conclusion.Based on results research conducted so can concluded that factors that become MSME supporters use digital payment is a fast and easy digital payment process, the payment process direct recorded in a way comprehensive complete matter This Of course will makes it easier in count activity sales and money direct enter to account trader with safe and also generational young now that's close with gadgets and following exists developments over time with increasingly technology advanced so with easy they understand and use system digital payments now this, and factors barriers that affect MSMEs' use digital payments are lack of knowledge about digital payments so Still choose still use payment cash, often happens disturbance network moment transactions and there are also problems with capital.